Analisis Pengaruh Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Beban Operasional Pendapatan Operasional (BOPO), dan Capital Adequacy Ratio (CAR) terhadap Return On Asset (ROA) pada Bank Umum yang terdaftar pada BEI (Studi kasus PT. Bank MNC, PT. BCA, dan PT. BTN [Persero] periode 2010-2014) - Ibram Pinondang Dalimunthe (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
Financial report aims to provide information regarding the financial position, performance and changes in financial position. In addition the bank’s financial statements are also aimed at decision making.This study examines whether the effect of the Loan to Deposit Ratio, Net Interest Margin, Operating Expenses Operating Income, and Capital Adequacy Ratio to Return On Assets in commercial banks on the Stock Exchange with a case study PT Bank MNC Internasional Tbk., PT Bank Central Asia Tbk., and PT Bank Tabungan Negara Tbk. (Persero) by using data on the period 2010-2014. The data was then tested using regression test panel fixed effect model. The authors found that there are significant variables simultaneously on Loan to Deposit Ratio, Net Interest Margin, Operating Expenses Operating Income, and Capital Adequacy Ratio on Return On Assets. Partial results of the study showed that the variables Loan to Deposit Ratio Significant and negative effect on Return On Assets, Net Interest Margin variable significant and positive impact on the Return On Assets, variable Operating Expenses Operating Income significant and negative impact on the Return On Assets, and variable Capital Adequacy Ratio significant and positive impact on the Return On Assets. The relationship between the independent variable on the dependent variable is equal to 97.8611%, which means that the remaining 2.1389% is influenced by other variables not included in the model.Based on research with panel data analysis, the authors found that there are individual effect that are fixed (fixed effect).